Effects of LED light quality on the growth characteristics and nutritional quality of hydroponic arugula - Zhou, Fujun; Wu, Hao (International Journal of Agricultural and Biological Engineering, 2025)
The global planting area of arugula (Eruca sativa Mill.) is increasing because of the unique flavor of this species. Excessive application of chemical fertilizers and pesticides is common in open-field cultivation of arugula, which leads to the accumulation of pesticide residue and nitrates in the leaves. Currently, arugula is mostly consumed as raw produce, increasing the importance of pesticide and pest-derived food safety issues. To improve the food safety and yield of arugula, we evaluated the effects of light quality from different LED light sources on the growth characteristics and nutritional quality of arugula plants hydroponically grown in an artificially illuminated plant factory. The arugula plants were grown under artificial LED light sources with different ratios of red and blue LED chips (3:1, 5:1, 7:1, 9:1), a photoperiod of 12 h/d, and a light intensity of 200 μmol/(m2∙s). White light was used as a control. The height, stem thickness, and leaf width of the arugula plants were measured every 5 d to generate curves of growth characteristics at different growth periods and to analyze the dynamic light quality needs of arugula. After 30 d of growth, the arugula plants were harvested, and the patterns of the effects of light quality on the growth characteristics and nutritional quality were examined. The results showed that red light had a significantly positive effect on the height, stem thickness, biomass accumulation, chlorophyll content, and soluble protein content of arugula. The arugula plants were tallest under the light with 9:1 red and blue LED chips ratio, but the effect on the soluble protein content was not significantly different from that under the 7:1 ratio, and the stem thickness and biomass accumulation were lower under the 9:1 ratio. Under the 7:1 red and blue LED chips ratio, arugula presented the greatest values of stem thickness, dry weight, fresh weight ratio, chlorophyll content, and soluble protein content. In addition, blue light promoted the synthesis of vitamin C. The light quality involving a 3:1 red and blue LED chips ratio led to a stocky plant morphology, which improved the storage and transportation ability of arugula plants. Keywords: Eruca sativa Mill., LED, light quality, growth characteristics, nutritional quality DOI: 10.25165/j.ijabe.20251804.6709 Citation: Zhou F J, Wu H. Effects of LED light quality on the growth characteristics and nutritional quality of hydroponic arugula. Int J Agric & Biol Eng, 2025; 18(4): 71–77.